Intracranial Hemorrhage in Term Infants - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
The authors identified 12 cases of symptomatic intracranial hemorrhage (ICH) among 23,000 infants born at the Beth Israel and Brigham and Women's Hospitals in Boston, MA, in 1982 and 1983.